Irving Finkel, 2014 The Ark Before Noah: Decoding the Story of the Flood, London: Hodder and Stoughton, ISBN 9781444757057, 421pp, 17 plates, many figures, £25.00. - Millard, Alan (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
None